2011
DOI: 10.1007/s00540-011-1264-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest after spinal anesthesia in a patient with neurally mediated syncope

Abstract: We present the case of cardiac arrest in a patient with neurally mediated syncope (NMS). A 66-year-old male patient was scheduled to undergo right inguinal hernioplasty. He had a history of syncope, which occurred a few times a year in childhood and once a year recently. One minute after the second spinal injection, cardiac arrest (asystole) developed. Sinus rhythm was restored by cardiac massage and intravenous administration of atropine and ephedrine. The operation was cancelled. The patient was diagnosed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Spinal anesthesia is one of the most used anesthetic techniques, believed to be very safe, though severe complications may occur (Ishiyama et al 2012). The first cases of CA occurring after spinal block anesthesia were reported in the 1940s and since then, the ability of spinal anesthesia to cause cardiopulmonary arrest was considered (Arruda et al 2011).…”
Section: Spinal Anesthesia Fatalitiesmentioning
confidence: 99%
“…Spinal anesthesia is one of the most used anesthetic techniques, believed to be very safe, though severe complications may occur (Ishiyama et al 2012). The first cases of CA occurring after spinal block anesthesia were reported in the 1940s and since then, the ability of spinal anesthesia to cause cardiopulmonary arrest was considered (Arruda et al 2011).…”
Section: Spinal Anesthesia Fatalitiesmentioning
confidence: 99%
“…Yamaha in a study of the object by subject neurocardioscopic syncope after spinal anesthesia was performed. In this study, one of the causes of syncope, the movement of blood in the lower extremities is expressed, which then activates the sympathetic nervous system and thus severe bradycardia or asystole and syncope occur that cause bradycardia in patients due to the above results, although we can also have multiple causes [24,25].…”
Section: Discussionmentioning
confidence: 95%
“…Park et al [ 20 ] reported a case of vasovagal syncope after injecting 20 mL of 2% lidocaine plus 100 µg fentanyl through an epidural catheter. Ishiyama et al [ 21 ] presented a case of neurally mediated syncope following administration of spinal anesthesia. Alparslan et al [ 22 ] discussed a case of vasovagal syncope observed after administration of spinal anesthesia in the sitting position.…”
Section: Discussionmentioning
confidence: 99%